New Product Development Speed: Too Much of a Good Thing? - Chen,Jiyao; Reilly,Richard; Lynn,Gary (Journal of Product Innovation Management, 2012)
New product development speed has become increasingly important for managing innovation in fast-changing business environments. While the existing literature has not produced consistent results regarding the relationship between speed and success for NPD projects, many scholars and practitioners assert that increasing NPD speed is virtually always important to NPD success. The purpose of this study is to examine the implicit assumption that faster is better as it relates to NPS. From the perspectives of time compression diseconomies and absorptive capacity, the authors question the assumption that speed has a linear relationship with success. The authors further argue that time compression diseconomies depend on levels of uncertainty involved in NPD projects. Using survey data of 471 NPD projects, the hypotheses were tested by hierarchical regression analysis and subgroup polynomial regression. The results of this study indicate that NPD speed has a curvilinear relationship with new product success, and the nature of the speed-success relationship varies, depending on type and level of uncertainty. When turbulence or technological newness is high, the relationship is curvilinear but when uncertainties are low, the relationship is linear. In contrast, the results of this study suggest that a curvilinear relationship under conditions of low market newness but not when market newness is high. Discussion focuses on the implications of NPD speed under the different conditions of uncertainty.
Keywords: Strategy & Entrepreneurship